Identification of Plasmodium falciparum VAR2CSA peptides differentially recognized by IgG of multigravidae through epitope excision - Misal, Santosh A.; Renn, Jonathan P.; Morrison, Robert D.; Cowles, Matthew V.; Mahamar, Almahamoudou; Attaher, Oumar; Dicko, Alassane; Duffy, Patrick E.; Fried, Michal (Frontiers in Immunology, 2025)
BackgroundPlacental malaria is associated with adverse outcomes for both mothers and their newborn children. During pregnancy, Plasmodium falciparum–infected erythrocytes (IEs) that surface-express VAR2CSA can bind chondroitin sulfate (CSA) in intervillous spaces and sequester in the placenta. Women acquire antibodies to VAR2CSA during their first pregnancy, but functional antibodies that block IE adhesion and are associated with improved outcomes develop over 2-3 pregnancies. Currently, VAR2CSA is the leading pregnancy malaria vaccine candidate.MethodsTo identify and quantify epitopes differentially recognized by IgG of multigravidae that acquired anti-adhesion antibodies compared to primigravidae that did not, we applied epitope excision and multiplex isobaric labeling to quantify epitope recognition by naturally acquired antibodies.ResultsWhile primigravidae and multigravidae IgG reacted similarly to most epitopes, multigravidae IgG differentially recognized (Log2 fold change > 1, p < 0.05) ten epitopes conserved across multiple VAR2CSA alleles.ConclusionKnowledge of VAR2CSA epitopes preferentially recognized by immune multigravidae will be valuable for designing a VAR2CSA subunit vaccine.